Insight into humification of mushroom residues under addition of Rich-N sources: Comparing key molecular evolution processes using EEM-PARAFAC and 2D-FTIR-COS analysis. (1st March 2023) - Wang, Dingmei; Mao, Yilin; Mai, Liwen; Yu, Zhen; Lin, Jiacong; Li, Qinfen; Yuan, Jing; Li, Guoxue
Abstract: Accelerating the humification of organic solid waste is one of the most important issues in composting. This present study aims to study and compare the humification process of different rich-N sources (chicken manure, cattle manure, and urea) addition during the composting of mushroom residues, from macro physicochemical properties to micro humic molecular structure evolution process. The physicochemical elements and humic components were determined for evaluating the compost quality and humification degree as composting proceed. The coupled analysis of excitation-emission matrix with parallel factor analysis (EEM-PARAFAC) and two-dimensional correlation with Fourier transform infrared spectrum (2D-FTIR-COS) were used to characterize the functional molecular structure evolution of dissolved organic matter during humification process. The results indicated that the rank order for humification level were the treatments of chicken manure (HM), urea (UM), cattle manure (CM), and single mushroom residue treatment (CK), with their humification index of 22.18%, 22.05%, 18.47%, and 16.52%, respectively. Humic substance, humic acid, and fulvic acid were obtained the highest in HM treatment with contents of 35.41 ± 0.86%, 23.32 ± 1.57%, and 10.97 ± 0.52%, respectively. The rich-N source addition enhanced the degradation of protein-like and polysaccharides-like substances in dissolved organic matter, thus accelerating the humification process of mushroom residues. The key structure evolution of dissolved organic matter in the HM treatment, in which the CO and CC stretching of quinone, amide, or ketone, and the C–O stretching of polysaccharides may be responsible for the faster formation of humus compared to the other nitrogen treatments. In this study, redundancy analysis indicated that the total nitrogen (TN) and nitrate nitrogen (NO3 − -N) may be the potential indicators for determining the humification level as composting proceed. The result provides significant insight into the humification mechanism of mushroom residue under different types of nitrogen sources at the molecular level, and will be reference for improving the composting technique in practical field. Graphical abstract: Image 1 Highlights: The humification process was studied from element properties to molecular evolution. EEM-PARAFAC and 2D-FTIR-COS were combined to expound humus molecular structure evolution. Addition of N sources accelerated the mushroom residue humification process. Rapid reaction of polysaccharides and protein-like substances were the key factors.